2022
DOI: 10.3390/ph15091087
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology for Pediatric Retinoblastoma Therapy

Abstract: Retinoblastoma is a rare, sometimes hereditary, pediatric cancer. In high-income countries this disease has a survival rate approaching 100%, while in low- and middle-income countries the prognosis is fatal for about 80% of cases. Depending on the stage of the disease, different therapeutic protocols are applied. In more advanced forms of the disease, surgical removal of the entire globe and its intraocular contents (enucleation) is, unfortunately, necessary, whereas in other cases, conventional chemotherapy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 99 publications
0
16
0
Order By: Relevance
“…Due to their unique characteristics, including biocompatibility, MSNs have been investigated as a potential therapy for retinoblastoma. 84,85 One method of employing MSNs in treating retinoblastoma entails dosing them with a chemotherapeutic agent and directing them, particularly to cancer cells in the eye. MSNs' large surface areas, variable pore sizes, and capacity to be functionalized with targeting ligands make it possible for them to load medicines efficiently and bind to cancer cells specically, as shown in Fig.…”
Section: Mesoporous Silica Nanoparticlesmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to their unique characteristics, including biocompatibility, MSNs have been investigated as a potential therapy for retinoblastoma. 84,85 One method of employing MSNs in treating retinoblastoma entails dosing them with a chemotherapeutic agent and directing them, particularly to cancer cells in the eye. MSNs' large surface areas, variable pore sizes, and capacity to be functionalized with targeting ligands make it possible for them to load medicines efficiently and bind to cancer cells specically, as shown in Fig.…”
Section: Mesoporous Silica Nanoparticlesmentioning
confidence: 99%
“…7). 85 Studies have also reported these compounds to have fewer toxic effects than conventional chemotherapeutic agents. 85 However,…”
Section: Nanoparticles In Delivering Phytochemicals To Retinoblastoma...mentioning
confidence: 99%
See 2 more Smart Citations
“…PTT employs plasmonic metallic nanosystems or NIR dye, which convert the incident NIR light into light, thereby causing a localized ablation of the tumor cells [ 18 , 19 , 20 ]. Several studies have reported the use of photothermal therapy for the treatment of retinoblastoma [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. However, recent literature reports reveal that the tumor cells acquire inherent resistance to the heat that is induced via PTT through the activation of heat shock proteins (HSP).…”
Section: Introductionmentioning
confidence: 99%